Structure-activity relationship of a hemagglutinin from Moringa oleifera seeds - Katre, Uma V.; Suresh, C. G.; Khan, Mohammad Islam; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2008)
The hemagglutinin from the seeds of Moringa oleifera (MoL) agglutinates human as well as rabbit erythrocytes; the affinity for the latter is almost 250 times more than that for the former. MoL was inhibited by glycoproteins namely thyroglobulin, fetuin and holotransferin indicating the complex sugar specificity of the lectin. The protein is a homodimer with molecular mass of 14 kDa, subunits (7.1 kDa) linked by the disulfide bond(s). The secondary structure elements of MoL area-helix, 28%; beta-sheet, 23%; turn 20% and unordered 28%. While the activity and secondary structure were not affected at extreme pH and high temperature, they were drastically affected in presence of dithiothreitol at and above pH 7.0, indicating that disulfide linkages hold the active conformation of the protein. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: disulfide linkages; Moringa oleifera hemagglutinin; Secondary structure